Salud general y su influencia en el rendimiento académico de los estudiantes de sexo masculino de la Universidad Nacional de Loja, periodo marzo-julio 2014 - Agurto Torres, Andrea Gabriela (2015)
This research was made in order to identify the influence of mental health through the General Health Questionnaire in the academic performance of male students at the National University of Loja; measure the level of overall health of the population studied; for which we have applied the general health questionnaire to a large sample of students of students of the National University of Loja, with students from careers of Veterinary Medicine, Geology, Medicine, Forestry Engineering, Electromechanics, Dentistry, Law, Nursing, Economics, Environment, Public Administration, English and Agriculture, also get to set the level of General Health of each of the dimensions proposed by the scale of mental health, namely somatic symptoms related to tiredness and fatigue, heaviness, aching headaches, anxiety and insomnia self-determination, social dysfunction and severe depression; and determining the GPA obtained in the cycle from March to July 2014, the population sample mostly maintained an average age of 18-24 years, the instruments used are: mental health questionnaire, which measures the psychological well-being and ratings due to determine the level of students passing and fail the module in progress, which impacts in the Academic Performance of persons under investigation; throwing as severe depression results which maintains a high level of involvement in students Ia followed by anxiety and insomnia that limit adequate physical condition that determines the overall health of students in their unavailability to maintain sustainable academic development. KEYWORDS: Application valuation, psychological, psychosocial Links, Project of life, self-acceptance, severe depression